Remaking Communities and Adult Learning Social and Community-based Learning, New Forms of Knowledge and Action for Change - Evans, Rob; Kurantowicz, Ewa; Lucio-Villegas, Emilio (Brill, 2022)
What responses is adult education providing to the great global problems: climate change and the environment, populism and racism, gender inequality, social and economic inequality? The ESREA Research Network between Local and Global - Adult Learning and Communities and the authors collected here argue for socially engaged community-based research which promotes critical democracy and popular education and drives powerful research methodologies: participatory research, feminist research, ecological research activism, posthumanist research, and more. The first part of the book looks back and forwards to the contribution to adult learning and community development played by participatory research in the making and remaking of community and society. In the second part, the focus shifts to pedagogies of possibility and change, knowledge creation and the transformation of pedagogies of inclusion. The third part, on activism and change, turns its attention to the motivations for activism and their individual and collective forms of expression. The final part considers re-making and 'doing' society and community, in particular during the COVID-19 pandemic. For researchers interested in participatory and emancipatory social research, gender and biography research, or community-university research partnerships, Remaking Communities and Adult Learning presents adult learning as a site of resistance for sustainable and creative andragogic practice.